PLANNING FOR SOLAR PUBLIC STREET LIGHTING (PJUTS) ON DWIKORA ROAD, JAGOI BABANG SUB-DISTRICT - Muhammad, Roofi; Yandri, Yandri; Hiendro, Ayong (Faculty of Engineering, Universitas Tanjungpura, 2024)
Solar Public Street Lighting (PJUTS) utilises solar energy to reduce dependence on fossil fuels from PLN for public street lighting. With an emphasis on project capacity and total costs, this research examines the planning of solar-powered public street lighting in Dwikora Road, Jagoi Babang District. Research methods included technical and economic analysis. The research findings indicated that for a road with a length of 12,940 metres and a width of 5 metres, 325 light poles with a height of 7 metres are required. Three hundred twenty-five units of polycrystalline solar panels generate lighting with a panel capacity of 150 Wp, supported by a 12.8V 50 Ah LittoKala (LiFePO4) battery and a Solar Charge Controller type MPL1210. The total project cost is Rp 2,502,912,000, with an estimated lamp load energy of approximately 42,120 kWh per year. PJUTS Energy is expected to reduce dependence on fossil energy and promote environmental and economic sustainability in the region.